2018
DOI: 10.1016/j.meatsci.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of β-glucans in meat emulsions through an optimal mixture modeling systems

Abstract: The effects of β-glucans (βG) in beef emulsions with carrageenan and starch were evaluated using an optimal mixture modeling system. The best mathematical models to describe the cooking loss, color, and textural profile analysis (TPA) were selected and optimized. The cubic models were better to describe the cooking loss, color, and TPA parameters, with the exception of springiness. Emulsions with greater levels of βG and starch had less cooking loss (<1%), intermediate L* (>54 and <62), and greater hardness, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…In this study, the degree of selective denaturation of the basic protein areas in the myosin molecule was determined during storage process. This strengthens the idea that protein degradation may be associated with changes in transition temperatures (Rios‐Mera, Pinto, & Contreras‐Castillo, ; Vasquez Mejia et al, ).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…In this study, the degree of selective denaturation of the basic protein areas in the myosin molecule was determined during storage process. This strengthens the idea that protein degradation may be associated with changes in transition temperatures (Rios‐Mera, Pinto, & Contreras‐Castillo, ; Vasquez Mejia et al, ).…”
Section: Resultssupporting
confidence: 83%
“…According to our study DSC results, the transition peak I was myosin, II sarcoplasmic proteins‐ with collagen, and peak III as actin (Addis et al, ; Akköse, ; Hastings, Rodger, Park, Mathews, & Anderson, ; Howell, Matthews, & Donelly, ). The peak I, myosin degradation in the degradation of the observed proteins in fish meat, is associated with collagen and sarcoplasmic breakdown between the second pass and the final peak with actin cast (Vasquez Mejia et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In table 2, it can be seen that the interaction between elephant foot yam flour and soybean oil addition, with higher flour addition (20%) showed higher texture at all soybean oil concentrations in this research. This showed that the soybean oil hand an important role to maintain the protein emulsion stability to bind protein molecules (Mejia et al, 2018). The polysaccharides contained in elephant foot yam flour are starch and foot fiber.…”
Section: Physical Propertiesmentioning
confidence: 98%